Psychosocial and health behavioural characteristics of longitudinal physical activity patterns: a cohort study from adolescence to young adulthood - Aira, Tuula; Vasankari, Tommi; Heinonen, Olli J; Korpelainen, Raija; Kotkajuuri, Jimi; Parkkari, Jari; Savonen, Kai; Toivo, Kerttu; Uusitalo, Arja; Valtonen, Maarit; Villberg, Jari; Vähä-Ypyä, Henri; et al. (BMC public health, 2023)
Background The decline in physical activity (PA) during adolescence is well-established. However, while some subgroups of adolescents follow the general pattern of decreased activity, others increase or maintain high or low activity. The correlates and determinants of different PA patterns may vary, offering valuable information for targeted health promotion. This study aimed to examine how psychosocial factors, health behaviours, and PA domains are associated with longitudinal PA patterns from adolescence to young adulthood. Methods This prospective study encompassed 254 participants measured at mean ages 15 and 19. Device-measured moderate-to-vigorous PA was grouped into five patterns ( activity maintainers, inactivity maintainers, decreasers from moderate to low PA, decreasers from high to moderate PA, increasers ) via a data-driven method, K-Means for longitudinal data. Multinomial logistic regression was used to analyse the associations between health behaviours, psychosocial factors, PA domains, and different PA patterns. Results A lack of sports club participation characterised inactivity maintainers throughout adolescence. Difficulties in communicating with one’s father at age 15 were associated with higher odds of belonging to inactivity maintainers and to decreasers from moderate to low PA . Lower fruit and vegetable consumption at age 19 was also related to increased odds of belonging to the groups of inactivity maintainers and decreasers from moderate to low PA. S moking at age 19 was associated with being a decreaser from moderate to low PA. Conclusions Diverse factors characterise longitudinal PA patterns over the transition to young adulthood. Sports club participation contributes to maintained PA. Moreover, a father-adolescent relationship that supports open communication may be one determinant for sustained PA during adolescence. A healthier diet and non-smoking as a young adult are associated with more favourable PA development.